2012
DOI: 10.1038/pj.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magic angle spinning on T1H of SBR studied by solid state 1H NMR

Abstract: We have investigated the influence of the high centrifugal pressure caused by fast magic-angle spinning (MAS) on the molecular motion of styrene-butadiene rubbers (SBR) filled with SiO 2 (SBR/Si composite) though solid-state magic-angle spinning nuclear magnetic Resonance ( 1 H MAS NMR) measurements. Because the 1 H-1 H dipolar interaction of elastomers is weak compared with that of glassy polymers, a narrower 1 H linewidth is observed under fast MAS. The temperature dependence of the 1 H spin-lattice relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…However, the maximal centrifugal pressure in an NMR rotor acts on the ZrO 2 rotor wall during MAS (∌1,500 bar at 17.0 kHz MAS in a 3.2 mm rotor, F. Engelke, lecture notes of EBSA solid-state NMR school 2014). The pressure value acting on the protein is even lower and is estimated between 60 and 91 bars (Kawamura et al, 2007;Asano et al, 2012). Consequently no pressure-induced protein degradation is expected (where this would, for example, occur at the 2,500 bar for ubiquitin (Charlier et al, 2018), 3,000 bar for PHS SNase (Roche et al, 2012), or 1,000 bar for spinach photosystem II (Tan et al, 2005)).…”
Section: Resultsmentioning
confidence: 99%
“…However, the maximal centrifugal pressure in an NMR rotor acts on the ZrO 2 rotor wall during MAS (∌1,500 bar at 17.0 kHz MAS in a 3.2 mm rotor, F. Engelke, lecture notes of EBSA solid-state NMR school 2014). The pressure value acting on the protein is even lower and is estimated between 60 and 91 bars (Kawamura et al, 2007;Asano et al, 2012). Consequently no pressure-induced protein degradation is expected (where this would, for example, occur at the 2,500 bar for ubiquitin (Charlier et al, 2018), 3,000 bar for PHS SNase (Roche et al, 2012), or 1,000 bar for spinach photosystem II (Tan et al, 2005)).…”
Section: Resultsmentioning
confidence: 99%
“…Pressure-induced protein structure, cell-volume changes, pharmaceutical samples and rubbers have all been characterized using fast MAS techniques. [20][21][22][23][24][25] In this study, we demonstrated that the significant changes in the dynamics of protein induced by fast sample spinning occur in the vicinity of retinal. In our previous studies, we assigned the major signals observed for bR by analyzing the associated local conformation and dynamics using a site-directed solid-state NMR approach.…”
Section: Introductionmentioning
confidence: 64%
“…42 For example, in a recent study of styrene-butadiene rubbers, a 3.2 mm outer diameter rotor with an inner diameter of 2 mm was predicted to exert a pressure of 9.5 MPa with n r ÂŒ 25 kHz, a much higher value than the pressure of 1.0 MPa exerted with a slower n r ÂŒ 10 kHz. 43 Cryogenic cooling of probe electronics to reduce thermal noise is widely employed in solution-state NMR and is used extensively in applications to drug discovery and development. Cooling of the probe coil and electronics to 25 K, or in some cases higher temperatures, while maintaining the sample at room temperature, yields signal-to-noise ratio (SNR) enhancements on the order of 2 to 4 times that of a conventional probe by reducing thermal electronic noise (see also Chapter 5 for in vivo applications of a cryogenic coil).…”
Section: Instrumentationmentioning
confidence: 99%